Hypnoparenting As A Way For Parents To Build Positive Personality In Children - Arina Firdaningrum; Afrida Muarifa; Laelatus Soimah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
The development of civilization in this century is marked by many behaviors that show a negative personality. The formation of a child's personality needs to start early. Parents are an initial basis of life for every human being. So the family especially parents have the most important role to build a positive personality in children. The purpose of this paper is to explain the concepts, ways, and the right time to do Hypnoparenting. Hypnoparenting is a method of parenting, educating, and caring for children which is done by the method of hypnosis. How to do Hypnoparenting is by suggesting children with sentences that can make children confident and with words that are positive. There are some of the best times to consider in conducting Hypnoparenting method. The method used in this research is literature study. Sources taken are based on scientific journals and research reports relating to the problem